ESSENTIAL CHARACTERISTICS AND STRUCTURAL COMPONENTS OF THE COMMERCIAL BANKS EMPLOYEE’S EMOTIONAL MATURITY - Vashchenko, Iryna; Onufriieva, Liana (PSYCHOLOGICAL JOURNAL, 2018)
The review and analysis of the problem on the emotional maturity of a personality are presented in the article. The notion of the emotional maturity in the works of prominent modern psychologists is substantiated. It is shown that the development of emotional maturity is important for socionomic professions specialists, including bank employees. The psychological features of the commercial banks employees’ emotional maturity are proved to be as follows: emotionally mature workers have high and average emotional stability; low, optimal characteristics of negative emotionality; high level of positive emotionality; high level of emotional self-consciousness; emotionally immature workers have low emotional stability; high level of negative emotionality; low level of positive emotionality and the emotional self-consciousness formation. The criteria of the emotional maturity of a personality are shown to be: sensitivity, openness to emotional experience; awareness; adequacy of manifestation and expression of feelings (correspondence to the external situation, internal state); psychological well-being (self-confidence, life satisfaction, lack of psychosomatic symptoms); mature ways of transforming emotions (sublimation, humor, creativity); arbitrariness (the ability to manage personal emotional experiences and personal behavior). The indicators of emotional immaturity are established to be: a) low emotional stability; b) high level of negative emotionality; c) low level of positive emotionality; d) low level of emotional self-consciousness formation. The emotional immaturity of employees is studied to lead to internal conflicts, the lack of contact with their feelings and desires, inadequate self-expression, the lack of psychological well-being, maladaptation in the outside world, disharmonious relationships with others, low quality of professional activities, low level of communicative qualities, and the result is the failure of the activities, deterioration of the quality of bank customer service. Therefore, it is advisable to work with this category of bank employees, aimed at developing their emotional intelligence, forming the ability to manage emotions and regulate behavior that optimizes the formation of their emotional maturity.